2022
DOI: 10.1002/app.53558
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow percolation threshold biodegradable PLA/PBS/MWCNTs with segregated conductive networks for high‐performance electromagnetic interference shielding applications

Abstract: The formation of dense and complete conductive networks in the electromagnetic interference (EMI) shielding composite is the basis for its excellent EMI shielding performance. In this work, biodegradable poly (lactic acid)/poly (butylene succinate)/multi‐walled carbon nanotubes (PLA/PBS/MWCNTs) nanocomposites with segregated structures were successfully prepared via melt blending. Due to the successful preparation of segregated structures and the fact that MWCNTs were mainly dispersed in the PBS phase, an ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The specific SE value (SSE/ t ) is deployed to equate EMI shielding performance, and it links with three primary parameters (EMI SE, thickness, and density). A recently reported bio-based, biodegradable polymer composite of poly­(lactic acid) (PLA)/poly­(butylene succinate)/MWCNTs has a total EMI SE of 27.56 dB . Furthermore, it has been observed that the total EMI SE of PLA/Graphene nanocomposites reached a maximum value of 15.5 dB in X-bands at 15 wt % graphene loading .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific SE value (SSE/ t ) is deployed to equate EMI shielding performance, and it links with three primary parameters (EMI SE, thickness, and density). A recently reported bio-based, biodegradable polymer composite of poly­(lactic acid) (PLA)/poly­(butylene succinate)/MWCNTs has a total EMI SE of 27.56 dB . Furthermore, it has been observed that the total EMI SE of PLA/Graphene nanocomposites reached a maximum value of 15.5 dB in X-bands at 15 wt % graphene loading .…”
Section: Resultsmentioning
confidence: 99%
“…A recently reported bio-based, biodegradable polymer composite of poly(lactic acid) (PLA)/poly(butylene succinate)/MWCNTs has a total EMI SE of 27.56 dB. 43 Furthermore, it has been observed that the total EMI SE of PLA/Graphene nanocomposites reached a maximum value of 15.5 dB in X-bands at 15 wt % graphene loading. 44 In another study, carbon nanofiber mat shielding effectiveness of 52.2 dB has been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cells were nucleated around the interface between PLA and PBS, resulting in an open-cell morphology compared to the closed-cell morphology of neat PLA foam. Tian et al [445] prepared biodegradable PLA/PBS/multi-walled carbon nanotube (MWCNT) nanocomposites with segregated structures by melt blending. They reported that the MWCNTs were mainly dispersed in the PBS phase, which resulted in an ultralow percolation value of 0.071 vol%.…”
Section: Biodegradable Polymer Blendsmentioning
confidence: 99%
“…Another non‐negligible point is the impedance mismatch between conductive filler and polymer matrix, which is also a key factor in achieving high shielding performance 40,41 . Recently, constructing multiple interfaces have been well demonstrated to improve EMI SE of CPCs, such as porous/foam structure, 6,42,43 layered structure, 44,45 multiple phase blends, 46–49 segregated structure 50,51 . It is the multiple interfaces that increase the reflection/scattering and interfacial conduction of electromagnetic waves, resulting in an improved EMI SE.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Recently, constructing multiple interfaces have been well demonstrated to improve EMI SE of CPCs, such as porous/foam structure, 6,42,43 layered structure, 44,45 multiple phase blends, [46][47][48][49] segregated structure. 50,51 It is the multiple interfaces that increase the reflection/scattering and interfacial conduction of electromagnetic waves, resulting in an improved EMI SE. Therefore, a tailored conductive network and matrix structure in CPCs is of great necessity in obtaining desirable EMI SE.…”
Section: Introductionmentioning
confidence: 99%